2008
DOI: 10.1111/j.1365-3091.2007.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Pleistocene wet aeolian dune and interdune accumulation, S. Pedro da Maceda, north‐west Portugal

Abstract: Outcrops and cored/counter‐flushed boreholes in the coastal area between Espinho and Aveiro (north‐west Portugal) were investigated to reconstruct the changing patterns of sedimentation during the Late Pleistocene–Holocene. To obtain a common comparison basis, the grain‐size data from outcrop and borehole samples were analysed. The outcrops and the cored parts of the boreholes were dated by radiocarbon and optically stimulated luminescence. The results show that, on top of pebble‐rich beds of fluvial origin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 33 publications
(68 reference statements)
3
33
0
3
Order By: Relevance
“…The S. Domingos Sands and Silts (U10) and the Ribeira de Portela Sands (U12) reveal climatic conditions favourable to edaphogenesis (U10) and fluvial drainage reestablishment (U12), which may have occurred between z 32 and z 28 ka. This evidence agrees with Granja et al (2008), who reported successions of small fluvial systems progressively covered by wet aeolian accumulations during the first half of MIS 3. Pérez-Alberti et al (2009) described paleosols on the Galician coast, dated between z 32 and z 25 ka.…”
Section: Paleoenvironments and Ages Of The Sedimentary Unitssupporting
confidence: 93%
See 1 more Smart Citation
“…The S. Domingos Sands and Silts (U10) and the Ribeira de Portela Sands (U12) reveal climatic conditions favourable to edaphogenesis (U10) and fluvial drainage reestablishment (U12), which may have occurred between z 32 and z 28 ka. This evidence agrees with Granja et al (2008), who reported successions of small fluvial systems progressively covered by wet aeolian accumulations during the first half of MIS 3. Pérez-Alberti et al (2009) described paleosols on the Galician coast, dated between z 32 and z 25 ka.…”
Section: Paleoenvironments and Ages Of The Sedimentary Unitssupporting
confidence: 93%
“…Later, other studies were carried out by Alves (1989Alves ( , 1995Alves ( , 1996 and Meireles (1992). In the adjacent coastal areas of Galicia and Neiva-Aveiro, several studies on the Pleistocene and Holocene deposits were also made: Granja (1990), Granja and Carvalho (1991, 1993, Carvalho et al (1995Carvalho et al ( , 2006, , Granja et al ( , 1999Granja et al ( , 2008Granja et al ( , 2010, Granja (1997, 2003), Groot and Granja (1998), Pérez-Alberti et al (1998), Pagés (2000, 2007), Blanco-Chao et al (2002, 2003, Fábregas Valcarce et al (2003), Araújo (2001Araújo ( , 2004Araújo ( , 2005Araújo ( , 2008, Araújo et al (2003), Garcia-Amorena et al (2007), Thomas et al (2008), Araújo and Gomes (2009) and Ribeiro et al (2010Ribeiro et al ( , 2011. This paper focuses on the geomorphological and sedimentological characteristics of a Pleistocene coastal terrace staircase of NW Portugal, covered by extensive late Pleistocene to Holocene sedimentary units.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a podzol was deposited on the Pleistocene dunes located along Espinho -Ovar between 2.7 and 2 cal ka BP, suggesting reduced aeolian activity (Fig. 1) (Granja et al 2008). These results suggest the onset of several lagoonal environments over time, although it is not clear whether there was a single barrier extending alongshore the entire bay or several barriers enclosed the documented lagoons.…”
Section: Episodes Of Shoreline Progradation and Stabilitymentioning
confidence: 39%
“…Alternatively, evidence of ephemeral lagoons and landwards shoreline translation during the mid-late Holocene have been reported along the north-central coast of Portugal (Granja et al , 2008(Granja et al , 2010Granja 1999Granja , 2000Bernardes & Rocha 2007;Danielsen et al 2012). These results suggest a scenario of barrier evolution for highenergy and linear coasts characterized by landwards shoreline translation since the mid Holocene, when sea level reached its present position (Vis et al 2010a;Leorri et al 2013).…”
mentioning
confidence: 76%
See 1 more Smart Citation